Evaluation of Mixing Efficacy of Carriers for Supplemental Nutrient Premixes in Animal Feed - Dalton Holt; Charles G. Aldrich (Kansas Agricultural Experiment Station Research Reports, 2021)
Animal feed is commonly formulated with vitamin and mineral premixes to supply the micronutrient requirements of the animal. Premixes typically require carriers which act as a delivery system for micronutrients to aid in uniformity, dilution, and dispersibility across the entire mix. However, little information is available regarding how different carriers might influence the dispersion of nutrients throughout a premix. Therefore, the main objective was to develop a method to systematically evaluate the mixing efficacy of different carriers in a premix formulation. A currently established analysis of mixer uniformity was adapted and repurposed for the evaluation of the premix carriers, rice hulls, pea fiber, and soy hulls. These carriers were evaluated in duplicate 40-lb batch sizes using a single-shaft, double ribbon horizontal mixer. Additionally, these carriers were described based on their physical properties and flow behavior. For the mixer efficacy evaluation, pea fiber had the largest coefficient of variation (CV) (17.08%). Rice hulls, which are the industry standard, and soy hulls were similar to one another (6.02 and 5.36%, respectively) and had acceptable CV. Soy hulls had the largest mean particle size (802.46 μm ± 2.04), followed by pea fiber (458.42 μm ± 2.84), and rice hulls had the smallest mean particle size (339.35 μm ± 1.79). Soy hulls had the largest critical orifice diameter (COD), followed by pea fiber, and COD was smallest for rice hulls, (30, 28, and 20 mm, respectively). Pea fiber had the largest angle of repose at 41.00° and was followed closely by rice hulls at 40.24°. Soy hulls had shallowest angle at 35.28°. The particle size analysis, COD, and angle of repose give useful indications of an ingredient’s handling behavior. However, there is no easily discernible relationship between these tests and mixing efficacy of these carriers. This supports the utility of a separate analysis to evaluate mixing efficacy for specific ingredients. Rice hulls are the industry standard and continue to rank better on numerous metrics than other carriers, including their lower cost and improved ingredient-handling capabilities. Rice hulls and soy hulls also had better mixing uniformity, indicating that these two ingredients would better facilitate the distribution of nutrients across a premix. However, some sectors of the feed/ pet food industry have pushed to remove cereal grains and/or soy from their products. With these market demands, feed manufacturers may need to find alternatives to the more traditional ingredients that can be evaluated by these techniques.
Keywords: Carriers; Premix; Mixing; Rice; Pea; Soy; Fiber; Hulls